BCI Performance and Brain Metabolism Profile in Severely Brain-Injured Patients Without Response to Command at Bedside - Annen, Jitka; Blandiaux, Séverine; Lejeune, Nicolas; Bahri, Mohamed A.; Thibaut, Aurore; Cho, Woosang; Guger, Christoph; Chatelle, Camille; Laureys, Steven (Frontiers in Neuroscience, 2018)
Detection and interpretation of signs of ‘covert command following’ in patients with disorders of consciousness remains a challenge for clinicians. In this study, we used a tactile P3-based BCI in 12 patients without behavioral command following, attempting to establish ‘covert command following’. These results were then confronted to cerebral metabolism preservation as measured with glucose PET (FDG-PET). One patient showed ‘covert command following’ (i.e., above-threshold BCI performance) during the active tactile paradigm. This patient also showed a higher cerebral glucose metabolism within the language network (presumably required for command following) when compared with the other patients without ‘covert command-following’ but having a cerebral glucose metabolism indicative of minimally conscious state. Our results suggest that the P3-based BCI might probe ‘covert command following’ in patients without behavioral response to command and therefore could be a valuable addition in the clinical assessment of patients with disorders of consciousness.